In Defence of Indigenous Participation in Capitalism: How Athabasca Chipewyan First Nation Demands Rights and Resources from the Liberal Democratic Settler-State while also Challenging the Imposition of Colonial Rule - Sommers, L. Javed (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2017)
Much Indigenous studies scholarship asserts that Indigenous peoples must reject capitalism. On the other hand, many (scholars and non-scholars alike) assume that the success of Indigenous communities depends on their willingness to uncritically embrace capitalism. Utilizing Kevin Bruyneel's The Third Space of Sovereignty, this article argues that First Nations can both demand "rights and resources from the liberal democratic settler-state" and challenge "the imposition of colonial rule." In other words, First Nations can simultaneously participate in capitalism and further their sovereignty, and Athabasca Chipewyan First Nation provides an example of how this might be done.